A Case of Ruptured Splenic Artery Aneurysm in Pregnancy - Elizabeth K. Corey; Scott A. Harvey; Lynnae M. Sauvage; Justin C. Bohrer (Case Reports in Obstetrics and Gynecology)
Background. Rupture of a splenic artery aneurysm is rare complication of pregnancy that is associated with a significant maternal and fetal mortality. Case. A multiparous female presented in the third trimester with hypotension, tachycardia, and altered mental status. A ruptured splenic artery aneurysm was discovered at the time of laparotomy and cesarean delivery. The patient made a full recovery following resection of the aneurysm. The neonate survived but suffered severe neurologic impairment. Conclusion. The diagnosis of ruptured splenic artery aneurysm should be considered in a pregnant woman presenting with signs of intra-abdominal hemorrhage. Early intervention by a multidisciplinary surgical team is key to preserving the life of the mother and fetus.